'If rich people gave more money to poor people': Young people's perspectives on reducing offending and implications for social citizenship. (March 2020) - Larkins, Cath; Wainwright, John
Highlights: Innovative participatory research with children in contact with youth justice systems. Offending reduces when children and their rights are respected. Reducing offending requires social provision of resources to children and families. Understand the claims for justice in children's acts of citizenship and dissent. Abstract: This paper reports the perspectives of children in contact with five youth offending teams (YOT) in the North of England. Through participatory research, four children in custody designed research tools to guide adult researchers undertaking interviews with 46 children in YOT settings and analysed initial findings. Interviews focused on 'what helps you stop offending' identified worker engagement with children and their families to build relationships and access to social resources. This reverses standard perspectives and challenges workers to effectively engage. Their aspirations and experiences of rights and responsibilities are explored through a critical lens of lived and social citizenship.